1998
DOI: 10.1128/mcb.18.9.5062
|View full text |Cite
|
Sign up to set email alerts
|

Capped mRNA Degradation Intermediates Accumulate in the Yeast spb8-2 Mutant

Abstract: mRNA in the yeast Saccharomyces cerevisiae is primarily degraded through a pathway that is stimulated by removal of the mRNA cap structure. Here we report that a mutation in the SPB8 (YJL124c) gene, initially identified as a suppressor mutation of a poly(A)-binding protein (PAB1) gene deletion, stabilizes the mRNA cap structure. Specifically, we find that the spb8-2 mutation results in the accumulation of capped, poly(A)-deficient mRNAs. The presence of this mutation also allows for the detection of mRNA speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
160
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(168 citation statements)
references
References 43 publications
8
160
0
Order By: Relevance
“…Although the Lsm1p protein is related to core snRNP proteins, we found that it localized to the cytoplasm. As discussed below, these results and the ability of 3Ј poly(A) to suppress the LSM1-dependence of 1a-RNA3 interaction suggest that LSM1 may have even broader roles in cellular RNA metabolism than a previously identified contribution to mRNA decapping (26).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although the Lsm1p protein is related to core snRNP proteins, we found that it localized to the cytoplasm. As discussed below, these results and the ability of 3Ј poly(A) to suppress the LSM1-dependence of 1a-RNA3 interaction suggest that LSM1 may have even broader roles in cellular RNA metabolism than a previously identified contribution to mRNA decapping (26).…”
Section: Discussionmentioning
confidence: 84%
“…Lsm1p interacts with some other Sm-like proteins but not with snRNAs (24,25). Lsm1p mutation increases the accumulation of capped, poly(A)-deficient mRNAs, indicating a role for Lsm1p in mRNA decapping, which follows mRNA deadenylation and precedes mRNA degradation (26).…”
mentioning
confidence: 99%
“…Seven of these, Lsm2 -Lsm8, have been shown to interact with U6 snRNA and facilitate formation of U4/U6 RNA duplexes (Achsel et al, 1999). Recent reports demonstrated that yeast Lsm1 protein affects mRNA metabolism, particularly mRNA decapping and degradation (Boeck et al, 1998;Tharun et al, 2000) and it is possible that human Lsm1 regulates some specific genes related to tumour invasion or metastasis in prostate cancer cells. Further investigations are needed to clarify the molecular mechanisms of suppression of metastasis related to overexpression of the Lsm1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested by the finding that Lsm6 and Lsm8 were required for nuclear mRNA decay (Kufel et al, 2004). A specific role for Lsm1-Lsm7 concerns activation of mRNA decay in P-bodies; depletion of individual yeast Lsm proteins results in the accumulation of capped, oligoadenylated mRNA transcripts (Boeck et al, 1998;Bonnerot et al, 2000;Bouveret et al, 2000;Tharun et al, 2000). This specific Lsm complex is recruited alongside other decay factors to U-rich tracts by the protein Pat1, after its displacement of cap-binding translation factors (Parker & Sheth, 2007).…”
Section: Functional Roles For Lsm Proteinsmentioning
confidence: 98%